THE IDENTIFICATION AND REFLECTION IN ACCOUNTING OF THE PLUSES AND MINUSES WITHIN A CREDIT INSTITUTION - Diana Elena BRÎNZĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The cashier is the oldest banking activity and is present in almost all commercial banks, which created the picture that a banking society is first of all a cashier. This activity is a form of cash flow which passes from one customer to another through bank cashier. At the same time, cash is stored in the credit institution, used coins and banknotes are taken out and replaced by new ones whose authenticity is verified and are re-entered into circulation.